Reframing "participation" and "inclusion" in public health policy and practice to address health inequalities: Evidence from a major resident‐led neighbourhood improvement initiative. (9th September 2018) - Lewis, Susan; Bambra, Clare; Barnes, Amy; Collins, Michelle; Egan, Matt; Halliday, Emma; Orton, Lois; Ponsford, Ruth; Powell, Katie; Salway, Sarah; Townsend, Anne; Whitehead, Margaret; et al.
Abstract: There is a need for greater conceptual clarity in place‐based initiatives that seek to give residents of disadvantaged neighbourhoods more control over action to address the social determinants of health inequalities at a local level. In this article, we address this issue as it relates to the concepts of participation and inclusion. We draw on qualitative data generated during the first phase of the Communities in Control Study, a longitudinal multisite independent evaluation of the impact of Big Local on the social determinants of health and health inequalities. Big Local is a resident‐led area improvement initiative in England, funded by the UK Big Lottery Fund. Initiatives focused on community empowerment are increasingly prominent in public health policy and practice globally. Approaches emphasise the promotion of greater control over decisions and action among individuals, groups, and communities, particularly those living in disadvantaged circumstances. However, when it comes to participation and inclusion in taking action and making decisions, the field is characterised by conceptual confusion. This risks undermining the impact of these initiatives. While participation and inclusion are necessary conditions for empowerment and collective control, they are not necessarily sufficient. Sufficiency requires attention to the breadth of participation (i.e., to inclusion) and to the depth of participation (i.e., the extent to which it is experienced as empowering and ultimately enables the exercise of collective control over decisions and actions). In observing how different Big Local resident‐led partnerships across England are tackling the day‐to‐day challenges of engaging with their communities, we reveal the potential for policy and practice of reframing, and therefore clarifying (to highlight the different roles they have) the concepts of participation and inclusion in terms of depth and breadth.